Pengembangan Sistem Monitoring Infrastruktur Jaringan Sekolah Berbasis Web dengan API MikroTik - Izra Rafif Rabbani; Farizi Ilham; Adniel Rama Ezaputra; Muhammad Rizky (CV. Multi Kreasi Media, 2026)
The reliance of educational institutions on reliable internet connectivity has grown substantially with the widespread adoption of computer-based examinations. This situation demands network infrastructure that can be centrally monitored and controlled. This study develops a web-based network monitoring platform that leverages the MikroTik RouterOS programming interface to manage network infrastructure in a vocational school environment. The case study was conducted at SMKN 53 Jakarta, an institution operating 42 wireless access points across three different internet service providers. System design adopts the Waterfall software development methodology with a PHP, MySQL, and XAMPP technology stack. The resulting platform provides four core capabilities: live network traffic visualization, role-based hotspot user orchestration, dynamically configurable internet speed policy enforcement, and connection session audit logging. Evaluation demonstrates that this system successfully shifts the troubleshooting paradigm from reactive to proactive, while providing structured operational data for school management, particularly in preparing infrastructure for computer-based examination delivery.